Antimicrobial Treatment on a Catheter-Related Bloodstream Infection (CRBSI) Case Due to Transition of a Multi-Drug-Resistant Ralstonia mannitolilytica from Commensal to Pathogen during Hospitalization - Junyan Liu; Brian M. Peters; Ling Yang; Hui Yu; Donghua Feng; Dingqiang Chen; Zhenbo Xu (MDPI AG, 2022)
Despite its commonly overlooked role as a commensal, Ralstonia mannitolilytica becomes an emerging global opportunistic human pathogen and a causative agent of various infections and diseases. In respiratory illnesses, including cystic fibrosis and chronic obstructive pulmonary disease (COPD), R. mannitolilytica is also identified presumably as colonizer. In this study, one distinctive clone of R. mannitolilytica was firstly identified as colonizer for the first 20 days during hospitalization of a patient. It was then identified as a causative agent for catheter-related bloodstream infection with negative identification after effective treatment, verifying its transition from commensal to pathogen. In conclusion, we provide convincing evidence that during hospitalization of a patient, R. mannitolilytica transitioned from commensal to pathogen in the respiratory tract leading to catheter-related bloodstream infection (CRBSI).